Buccal mucosa cells as a diagnostic tool in patients with arrhythmogenic cardiomyopathy. (24th May 2021) - Van Der Voorn, SM; Driessen, HE; Van Lint, FHM; Bourfiss, M; Mirzad, F; El Onsri, L; Vos, MA; Van Veen, TAB
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Netherlands Cardio Vascular Research Initiative (CVON): the Dutch heart foundation Background: Arrhythmogenic cardiomyopathy (ACM) is predominantly caused by mutations in genes encoding desmosomal proteins (most often multiple different mutations in plakophilin-2), however also mutations in non-desmosomal proteins like phospholamban (PLN, PLNR14Del) are found. Previous investigations showed that plakoglobin protein levels and localization in cardiac tissue of ACM patients is disturbed and this could be a valuable additional tool to discriminate between non-affected family members and those being at risk during progression of the disease. Information about cardiac plakoglobin status can only be obtained via endocardial biopsies, however, this technique has major draw-backs and risks, and therefore an alternative is needed. A promising new non-invasive tool is the use of buccal mucosa cells (BMC), as it has been reported that effects of mutations in desmosomal proteins are additionally reflected in non-cardiac tissues like buccal mucosa smears that do also express those desmosomal genes. Purpose: To investigate the clinical usability of BMC as tool to classify patients at risk of developing ACM by comparing healthy controls with asymptomatic and symptomatic classical ACM patients, and patients carrying a PLNR14Del mutation. Methods and results: BMC of 84 human subjects, 33 ACM patients (19 males, 28 with a PKP2 mutation), 17 PLN patients (6 males) and 34 healthy controls (14 males), were collected on glass slides, fixed and labelled with anti-plakoglobin antibodies diluted 1:5.000, 1:10.000, 1:20.000 and 1:40.000, and scored for their membrane labelling. Data revealed that for each applied dilution, plakoglobin protein levels at the membrane were significantly reduced in BMC obtained from ACM patients compared to healthy controls. This effect appeared independent from age and sex of the patients. Furthermore, dilutions 1:5.000 and 1:10.000 showed a moderate correlation with the revised 2010 Task Force Criteria Score (TFC) which are commonly used for ACM diagnosis (Rs -0.67, n = 64, p <0.0001 and Rs -0.71, n = 64, p < 0.0001 resp.) In contrast, plakoglobin scores of PLN patients were similar to controls. Conclusion: On the population level, there is a significant reduction of plakoglobin protein in BMC membranes of ACM patients but not for patients bearing the PLNR14Del mutation when compared to healthy controls. However, for clinical diagnosis of the individual patient, this method is most likely not discriminative enough to distinguish patients from healthy controls, because of the high interindividual variability.